Reaction-based indicator displacement assay (RIA) for the colorimetric and fluorometric detection of hydrogen peroxide. Issue 6 (24th February 2017) - Sun, Xiaolong; Odyniec, Maria L.; Sedgwick, Adam C.; Lacina, Karel; Xu, Suying; Qiang, Taotao; Bull, Steven D.; Marken, Frank; James, Tony D.
Abstract : Reaction-based indicator displacement assay for the optical cycle-monitoring of hydrogen peroxide. Abstract : Based on the complexation of phenylboronic acid (PBA) with Alizarin Red S (ARS), we developed a new chemosensor for the detection of hydrogen peroxide (H2 O2 ) in aqueous media. This platform has demonstrated its ability to detect H2 O2 via colorimetric, fluorometric, and electrochemical measurements. The experimental observations reveal that the system displays a red-shifted visible colour change, on–off fluorescence response indicating release of indicator (ARS) and turn-on electrochemical signal indicating generation of phenol, after reaction with H2 O2 . With this work we have demonstrated that our reaction-based indicator displacement assay (RIA) systems, can be employed as an assay for H2 O2 and hydrogen peroxide-related species for environmental and physiological detection.